Determinants of symptom burden related to bowel preparation for colonoscopy. Issue 11 (November 2022) - Collatuzzo, Giulia; Fuccio, Lorenzo; Frazzoni, Leonardo; Radaelli, Franco; Hassan, Cesare; Fabbri, Carlo; Cadoni, Sergio; Laterza, Liboria; Anderloni, Andrea; Binda, Cecilia; La Marca, Marina; Montale, Amedeo; et al.
ABSTRACT: Background: Symptoms developing during bowel preparation are major concerns among subjects who refuse the procedure. Aims: We aimed to explore the determinants of symptoms occurring during preparation among patients undergoing elective colonoscopy. Methods: This is a prospective multicenter study conducted in 10 Italian hospitals. A multidimensional approach collecting socio-demographic, clinical, psychological and occupational information before colonoscopy through validated instruments was used. Outcome was a four-category cumulative score based on symptoms occurring during preparation, according to the Mayo Clinic Bowel Prep Tolerability Questionnaire, weighted by intensity. Missing values were addressed through multiple imputation. Odds ratios (OR) and 95% confidence intervals (CI) were estimated through multivariate logistic regression models. Results: 1137 subjects were enrolled. Severe symptoms were associated with female sex (OR=3.64, 95%CI 1.94-6.83), heavier working hours (OR=1.13, 95% CI=1.01-1.25), previous gastrointestinal symptoms (OR=7.81, 95% CI 2.36-25.8 for high score), somatic symptoms (OR=2.19, 95% CI=1.06-4.49 for multiple symptoms), day-before regimen (OR=2.71, 95%CI 1.28-5.73). On the other hand, age ≥60 years (OR=0.10, 95% CI 0.02-0.44) and good mood (p=0.042) were protective factors. A high-risk profile was identified, including women with low mood and somatic symptoms (OR=15.5, 95%CI 4.56-52.7). Conclusions: We identified previously unreported determinants of symptoms burdening bowel preparation and identified a particularly vulnerable phenotype. Symptoms during preparation especially impact heavier working activity.